Research on the validate of wheat production in the context of measures entreprised for the extension of market mechanisms - Elena Cofas (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
Wheat occupies an important place in the food security strategy as it is characterized by its long-lasting consistency and by its suitability for a wide range of bakery products. The role of wheat in the food security strategy is also determined by low maintenance costs compared to other foods, with no need for refrigerated chains or costly installations. Being the main raw material in bakery products, wheat is the most important crop in grain production. The bearers of wheat supply are, on the one hand, agricultural producers, irrespective of their organization and, on the other hand, the wheat traders, the latter having recovered as carriers of the offer, because they are generic, a primary market for the marketing of wheat (when it goes from producers to traders or directly to processors) and subsequently at least a second stage of marketing between different traders or between traders and processors. The Common Agricultural Policy is mainly integrationist, to a greater extent than the internal market, where the harmonized standards have replaced them by only about 10% national ones. With regard to the CAP, national agricultural policies have been replaced, for the vast majority of agricultural production, by common rules for the functioning of markets and the marketing of products. For the implementation of common market regulation measures, the following instruments are used: prices, market intervention, financial aid, production quotas, common customs protection.
Keywords: O12; P50; Q18; Q57; 330; wheat; market; mechanisms; production; analyze